Sécheresse : urgence climatique ou urgence de la planification ? Perception du management de crise en Belgique - Kevin Thibaut; Nathalie Schiffino; Pierre Ozer (VertigO)
Droughts are becoming more frequent and intense everywhere. The recurrence of these events contributes to the climate emergency. Both are recognised. But does this lead to political anticipation and public management of water scarcity? Belgium has a well-developed emergency planning and crisis management system that is regularly implemented for unexpected incidents, but which appears to be poorly adapted to emerging and slow-onset risks such as droughts. Through the feedback of crisis management professionals at a local level, this study provides a critical view of the perception of this phenomenon within crisis management and proposes some ways of improving the management of water deficits. Analysis of the interviews showed that: (1) multi-level governance in a federal political system with a complex distribution of competences complicates concerted public action in response to a risk with multiple impacts; (2) interest in droughts is highly dependent on the consequences effectively felt in the territory studied; (3) drought is perceived more as a one-off meteorological event than as a climatic emergency synonymous with a potential crisis to be planned. Nevertheless, this study reveals a growing awareness of actors on the field about the necessity to act towards droughts through the optimisation of public administrations, alert thresholds and specific emergency and intervention plans. A major difficulty remains: transforming this awareness into a political agenda, an essential step for a global and sustainable drought management.